2011
DOI: 10.3109/02713683.2011.627489
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sustained Release of PLC-Loaded Prednisolone Acetate Microfilm on Postoperative Inflammation in an Experimental Model of Glaucoma Filtration Surgery

Abstract: Subconjunctival insertion of a PA-loaded biodegradeable microfilm exhibit sustained release of PA to reduce postoperative inflammation and prolong bleb survival in rabbit GFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
3
13
0
Order By: Relevance
“…This pilot study further supports the potential usefulness of surgical implantation of sustained-released drug implants within the subconjunctival space to treat ocular inflammation [6], [7]. The subconjunctival location provides a surgically accessible place for insertion and if necessary, easily accessed for removal.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This pilot study further supports the potential usefulness of surgical implantation of sustained-released drug implants within the subconjunctival space to treat ocular inflammation [6], [7]. The subconjunctival location provides a surgically accessible place for insertion and if necessary, easily accessed for removal.…”
Section: Discussionsupporting
confidence: 67%
“…Prednisolone acetate achieves the highest aqueous concentration within 2 hours and maintains higher levels for 24 hours, compared to dexamethasone and other commonly used corticosteroids[5]. We have demonstrated in previous studies the anti-fibrotic and anti-inflammatory properties of a subconjunctivally implanted prednisolone acetate (PA)-preloaded microfilm in the rabbit model of subconjunctival scarring following glaucoma filtration surgery [6] and rat keratoplasty model[7]. Our in vivo studies have shown that PA-loaded poly[d,l-lactide-co-ε-caprolactone] (PLC) microfilms display good biocompatibility, feasibility, and desirable sustained drug release profiles, maintaining high anterior chamber PA levels at 76.7±5.9, 70.3±2.3, and 42.7±4.1 ng/mL at 2, 4, and 12 weeks, respectively[8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…A second explanation is that rabbits did not have increased IOP because they did not develop glaucoma in this study [38]. These results are consistent with data suggesting that IOP may not correlate with scarring in a subconjunctival wound healing animal model [29,38,39]. …”
Section: Discussionsupporting
confidence: 80%
“…The ideal dose and mode of delivery have yet to be determined. Microfilms are being developed to carry various types of ocular medications and may be a more standardized method to deliver steroids at the time of surgery 23,24. More study is needed to evaluate the ideal delivery of adjunctive steroids during AGV implantation to prevent encapsulation with its attendant poor hydraulic conductivity of aqueous humor.…”
Section: Discussionmentioning
confidence: 99%